Healing potential of the ointment based on the extract of the bark of Anacardium Occidentale L. containing solic lipid nanoparticles: A preclinical trial (Research, Society and Development, 2025)
The treatment of lesions represents a significant challenge for the public health system due to its high cost. Therefore, the present study evaluated the healing potential of two herbal formulations, one based on the hydroalcoholic extract of the inner bark of Anacardium occidentale (A.O), and the other containing the extract associated with solid lipid nanoparticles (SLN). Previous scientific studies have already demonstrated the pharmacological activities of A.O, such as healing, anti-inflammatory, analgesic and antimicrobial action. The hydroalcoholic extract obtained through the maceration process and continuous and static agitation was used. The nanoparticles were obtained through hot fusion and high shear homogenization, resulting in a microemulsion. The excisional lesions were performed with a 6 mm metal punch. Twenty animals were used in the experiment, distributed equally into four groups: Anacardium Occidentale Treatment Group (GT-AO), Anacardium Occidentale Treatment Group with Nanoparticles (GT-AON), Positive Control Group (GCP) using Fibrinase® as a parameter, and Negative Control Group (GCN). The developed formulation was tested in Swiss mice; preclinical analysis showed a significant acceleration in the healing process in GT-AON compared to GCP. The presentation of morphometric and macroscopic data indicate the comparison between all groups and their healing stages. The results corroborate studies that indicate the penetration of nanoparticles into the deepest layers and confirm that the association of the hydroalcoholic extract of A.O. with NLS technology enhances healing, suggesting a promising alternative for wound treatment.